A multi-objective optimization model of urban passenger transportation structure under low-carbon orientation considering participating subjects - Li, Xinguang; Zhan, Jun; Pan, Fuquan; Lv, Tong; Wang, Shen (Environmental science and pollution research international, 2023)
The optimization of urban passenger transport structure can effectively save energy and reduce the carbon emission of transport. However, the carbon emission and energy consumption generated by the construction of transport projects are worthy of attention. In this paper, a multi-objective optimization model of urban passenger transport structure oriented to low carbon is proposed considering passenger, operator, and construction. The optimal solution of the model is obtained based on the NSGA-II algorithm, and the validity of the model is verified with a case of Qingdao. The optimal ratio of Qingdao passenger traffic structure considering only the passenger perspective (PS), considering the passenger and operator (POS), and considering the three parties together (POCS) is obtained, respectively. The results show that the optimal structures obtained by the PS, POS, and POCS models increase the public transport passenger share by 12.74%, 20.74%, and 23.70%, compared with the actual values. From both the supply and demand sides, there has been an increase in the passenger share of public transport. The POS model is more suitable for solving structural optimization problems that do not involve construction carbon emissions in the short term. The POCS model is more suitable for long-term comprehensive structural optimization problems. The results of the study provide a reference basis for optimizing the urban passenger transport structure.